Development Of E-Module Based On Autoplay Media Studio 8 For Basic Machining Course For Undergraduate Students Of Mechanical Engineering Education, State University Of Malang - Muhammad Husin; Hakkun Elmunsyah; Widiyanti Widiyanti (International Journal of Information Systems and Technology, 2025)
In the current machining practicum, the teaching material module used for learning is not enough to facilitate the teaching and learning process about the machining process because the printed module which contains materials and pictures alone is not able to understand the machining practicum because the machining practicum requires direct observation from an educator's demonstration so that students better understand the process. To directly demonstrate the process to students requires more time and concentration, students are not necessarily able to understand it immediately. Sometimes students do not concentrate or forget and in order to better understand them, they need media assistance that can display material in the form of text, images, demonstrations in the form of audio and visual so that they can be studied independently and are easy to understand. Therefore, in order to make it easier for the delivery of material and demonstrations, interactive learning media in the form of electronic modules are needed that can be given to students to help facilitate the delivery of material or direct demonstrations in the form of text, images, audio and visuals to overcome them. Automedia Studio 8 was chosen as the media in the development of e-modules because it has many advantages in its use that do not need to install additional applications, as well as in the manufacture of products that can combine various types of files. The research and development that has been carried out has produced a product in the form of an e-module learning media for basic machining practicum based on Autoplay Media Studio 8 for undergraduate students of Mechanical Engineering Education, State University of Malang. The development of this learning media was developed using the ADDIE development model which consists of several stages, namely: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. Validation was carried out on material experts, media experts and test subjects, namely students. Based on the results of product validation on material experts, media experts, and users, data with a total average of 92.6% can be concluded that the e-module based on autoplay media studio that has been developed in the basic machining practicum course is categorized as feasible. It is recommended that in order to maximize learning, educators should explain the important points contained in the e-module directly on the machine. This module is only to support learning, not to replace practical work. How to do practical work can be learned from this e-module.